2009
DOI: 10.1061/(asce)gt.1943-5606.0000168
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Acoustic Method to Determine the Volumetric Water Content of Unsaturated Sands

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The corresponding degree of saturations at different suction heads were then determined. The testing procedure and measurements are thoroughly explained in Mohamed and Horoshenkov (2009) and Sharma and Mohamed (2003).…”
Section: Experimental Approachmentioning
confidence: 99%
“…The corresponding degree of saturations at different suction heads were then determined. The testing procedure and measurements are thoroughly explained in Mohamed and Horoshenkov (2009) and Sharma and Mohamed (2003).…”
Section: Experimental Approachmentioning
confidence: 99%
“…A number of studies have focused on the characterization of the speed and absorption of sound in different types of soils [7,8] and a few attempts to characterize sound propagation through the soil with different moisture contents [9,10], but these are in-situ rather than non-intrusive remote sensing or proximal sensing methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…A laboratory study [9,10] indicated that reflectance measurements can potentially give estimates of volumetric water content to  2%. A field measurement [16] where the moisture content was measured and varied used an acoustic impulse, with the amplitude of reflected sound doubling when the moisture content of grassland was changed from 10% to 35%.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have focused on the characterization of the speed and absorption of sound in different types of soils [10,11] and a few attempts to characterize sound propagation through the soil with different moisture contents [12,13], but these are in-situ rather than nonintrusive remote sensing or proximal sensing methodologies. One potential method of sensing the nature of the soil surface is to use acoustic reflection.…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic impedance is expected to have a clear increasing trend with a greater moisture content, which will plateau for saturated soil [10], [18,19]. A laboratory study [12,13] indicated that reflectance measurements can potentially give estimates of volumetric water content to ±2%. A field measurement [19], where the moisture content was measured and varied, used an acoustic impulse, with the amplitude of reflected sound doubling when the moisture content of grassland was changed from 10% to 35%.…”
Section: Introductionmentioning
confidence: 99%